Personality and Injury Risk Among Professional Hockey Players - Osborn, Zachary H (Kermanshah University of Medical Sciences, 2009)
BACKGROUND: Although much is known about risk for athletic injury, research on the roles of individual differences in personality and temperament on athletic injury has lagged. We hypothesized that professional athletes with high sensation-seeking and extraversion scores, and with low effortful control scores, would experience more injuries over the course of a season, would have more severe injuries, and would miss more total days of play. METHODS: Prospective design with questionnaire report at time one and injury tracking throughout an 18-week athletic season. Setting: Professional hockey team in the United States. Participants: Eighteen professional hockey players (ages 21-33). MEASUREMENT: Players completed self-report personality (Sensation-Seeking Scale, Form V) and temperament (the Adult Temperament Questionnaire) measures. Quantity and severity of injury, as well as playing time missed, were tracked for 18 weeks. RESULTS: On average, players experienced almost 6 injuries causing a loss of 10 playing days through the season. Those players scoring high on Boredom Susceptibility and Total Sensation-Seeking incurred more total injuries. Those scoring high on temperamental neutral perceptual sensitivity suffered more severe injuries. CONCLUSIONS: Athletes who suffered more injuries reported a preference for stimulating environments and boredom with non-stimulating environments. Injury severity was not correlated with sensation-seeking but was related to temperamental perceptual sensitivity. Implications for identification of injury-prone athletes, pre-injury training, and post-injury treatment are discussed.